2017
DOI: 10.1016/j.molmet.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid formation disrupts the balance between interleukin-1β and interleukin-1 receptor antagonist in human islets

Abstract: Objectivesβ-cell dysfunction and apoptosis associated with islet inflammation play a key role in the pathogenesis of type 2 diabetes (T2D). Growing evidence suggests that islet amyloid, formed by aggregation of human islet amyloid polypeptide (hIAPP), contributes to islet inflammation and β-cell death in T2D. We recently showed the role of interleukin-1β (IL-1β)/Fas/caspase-8 apoptotic pathway in amyloid-induced β-cell death. In this study, we used human islets in culture as an ex vivo model of amyloid formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Moreover, hIAPP transgenic mice fed a high-fat diet for 12 months have dramatically elevated proinflammatory gene expression in islets including Ccl2, Cxcl1, Nlrp3, Pycard, Casp1, Il1b, Tnf, Il6, Adgre1 and Itgax (Meier et al 2014), the expression of which is strikingly higher than the effect of high-fat diet alone, supporting the idea that IAPP aggregates are a majorand perhaps essential -trigger for islet inflammation. Consistent findings have recently been reported in cultured human islets, demonstrating that islet amyloid formation correlates with increased IL1B and decreased levels of endogenous IL1 receptor antagonist, IL1RN (Hui et al 2017). Furthermore, inhibition of hIAPP expression or aggregation in human islets reduced IL1B levels .…”
Section: Iapp Aggregates Induce Islet Inflammationsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, hIAPP transgenic mice fed a high-fat diet for 12 months have dramatically elevated proinflammatory gene expression in islets including Ccl2, Cxcl1, Nlrp3, Pycard, Casp1, Il1b, Tnf, Il6, Adgre1 and Itgax (Meier et al 2014), the expression of which is strikingly higher than the effect of high-fat diet alone, supporting the idea that IAPP aggregates are a majorand perhaps essential -trigger for islet inflammation. Consistent findings have recently been reported in cultured human islets, demonstrating that islet amyloid formation correlates with increased IL1B and decreased levels of endogenous IL1 receptor antagonist, IL1RN (Hui et al 2017). Furthermore, inhibition of hIAPP expression or aggregation in human islets reduced IL1B levels .…”
Section: Iapp Aggregates Induce Islet Inflammationsupporting
confidence: 87%
“…Moreover, LPS-primed cells subsequently treated with hIAPP secrete approximately 10-fold greater levels of IL1B than cells treated with hIAPP only (Westwell-Roper et al 2016); this may explain why others have not observed robust IL1B secretion from cells stimulated with hIAPP alone compared to LPS-primed cells treated with hIAPP (Masters et al 2010, Sheedy et al 2013. The relative contributions of hIAPP-induced NFKB1 and NLRP3 activation in islet inflammation and ensuing beta cell dysfunction in vivo remain to be tested, though IL1 clearly plays a critical role, as IL1 antagonism ameliorates inflammation, and beta cell dysfunction and death, in hIAPP transgenic mice and isolated human islets (Westwell-Roper et al 2011, Hui et al 2017, Jin et al 2017. Furthermore, though occurring through distinct mechanisms, both priming and NLPR3 activation by IAPP are likely to perpetuate a feed-forward inflammatory activation in macrophages; we found that IL1 signalling potentiates further IAPP-induced IL1B secretion (Westwell-Roper et al 2011), and IL1B has also been shown to enhance islet amyloid formation in both human and hIAPP transgenic islets .…”
Section: Iapp Priming Of Macrophagesmentioning
confidence: 99%
“…In islet cells, the expression of proinflammatory cytokines can be induced by the destruction of IAPP [41], hyperglycaemia [11,42] and free fatty acid stimulation [43]. The proinflammatory cytokines can cause b cell dysfunction [44] as well as dedifferentiation [45].…”
Section: Discussionmentioning
confidence: 99%
“…signalling through Toll-like receptors, caspase-1 is activated and cleaves pro-IL-1β to IL-1β [9][10][11] . Recent studies reported that NLRP3 inflammasome contributed to β cell dysfunction and death in type 1 and 2 diabetes 7,[12][13][14] . Furthermore, it affected the therapeutic effect of allogeneic organ transplantation 10 and worsened bacterial/viral infections 11 .…”
mentioning
confidence: 99%